Radio messaging frequency, information framing, and consumer willingness to pay for biofortified iron beans: Evidence from revealed preference elicitation in rural Rwanda - Oparinde, Adewale; Birol, Ekin; Murekezi, Abdoul; Katsvairo, Lister; Diressie, Michael Tedla; Nkundimana, Jean d’Amour; Butare, Louis (Wiley, 2016)
Iron deficiency is a public health problem in many developing countries. Iron‐biofortified varieties of commonly consumed staple crops have the potential to contribute to the daily iron requirements in diets. This paper examines consumer acceptance and willingness to pay (WTP) for two iron bean varieties in Rwanda: red iron bean (RIB) and white iron bean (WIB). Using the Becker‐DeGroot‐Marschak mechanism, the paper investigates the effect of (1) nutrition information; (2) information frame; and (3) the frequency of providing the information on consumer WTP. WTP estimations take into account social interaction and nonpayment effects. Results indicate that without information about the nutritional benefits of the two iron bean varieties, consumers are willing to pay a large premium for the RIB variety, but not for the WIB variety. The nutrition information provided has a significantly positive effect on the premium for each of the iron bean varieties. Results also indicate that the effects of how the information is framed on this premium are not statistically significant. However, providing the nutrition information three times versus once significantly increases consumer demand for the WIB variety. These findings could inform the design of efficient delivery and marketing strategies for iron bean varieties in Rwanda.